DECLINING STUDENT LEARNING MOTIVATION IN DIGITAL COSMETOLOGY, ETHNOBEAUTY, AND WELLNESS LEARNING: A HUMANISTIC THEORY PERSPECTIVE - Zahiya Syalaisha Riswanto; M Mamduh Winangun; Sri Usodoningtyas (Adornata : Ethnobeauty and Wellness Journal, 2026)
This study examines the problem of declining student learning motivation in the digital era from the perspective of humanistic theory, with specific attention to cosmetology, ethnobeauty, and wellness learning. The development of information technology has made learning resources more accessible; however, it also creates challenges such as digital distraction, instant culture, reduced face-to-face interaction, and weakened intrinsic motivation. This study uses a qualitative methodology with a library research approach by analyzing books, scientific journals, and academic articles related to learning motivation, digital learning, humanistic theory, beauty education, ethnobeauty, and wellness. The results indicate that declining motivation is influenced by high digital distraction, unmet psychological needs, lack of empathy in digital learning, and the dominance of task-oriented learning. From Maslow’s perspective, students’ needs for safety, belonging, esteem, and self-actualization may not be adequately fulfilled in digital learning environments. From Carl Rogers’ perspective, limited interpersonal communication, empathy, congruence, and unconditional positive regard can reduce meaningful learning. In cosmetology, ethnobeauty, and wellness education, this issue is important because students need not only cognitive understanding, but also practical skill, emotional sensitivity, client-centered communication, cultural awareness, and holistic wellness values. Therefore, technology integration should be balanced with humanistic learning strategies that strengthen empathy, reflection, professional identity, and meaningful engagement in beauty and wellness learning.